Archaeotourism and N-tiple Helix Model for Development of Continental Tourism of Croatia: The Case of Pannonian Croatia Region Arheoturizam i međusektorska suradnja u razvoju kontinentalnog turizma Hrvatske na primjeru Panonske Hrvatske - Durman, Aleksandar; Kukec, Ljiljana; Ćorić, Gordana (2014)
Croatian tourism has been challenged by global tourism trends and Croatian accession to the EU. Cultural heritage is widely recognized as strength in all Croatian tourism and strategic development documents, however, multisectoral cooperation for its commercialization and development of continental (inland) tourism is still lacking. The question is why numerous features of Croatian tourism have not been used for better positioning Croatia as the cradle of European culture. This paper addresses the need for recognition and acknowledgment of the significant role of archeology in the development of continental tourism. It also points out the need for cooperation between universities, institutions, business and civil society, and knowledge of the cultural and natural environment for the launch of the innovative development of tourist destinations, their commercialization and networking with the compatible regions of Europe. The starting point for this paper was found in the unique archaeological heritage of Pannonian Croatia and in the work of world known archaeologist Sir Arthur Evans in 1871. In order to develop and utilize this tourist potential, it is necessary to evaluate the key factors that influence the creation of innovative tourism product. Therefore, the PEST analysis was made. In addition to analyzing the existing intersectoral collaboration and analysis of Triple/Quadruple/Quintuple Helix dynamics, this paper offers recommendations for introducing commercial aspect of this particular tourism product and easier access to financial resources for its implementation The contribution of this paper is in identifying neglected potential of existing archaeological heritage as advantage for the development of continental tourism, placing the same in the context of crosssectoral cooperation, and pointing towards the need for strengthening cooperation in achieving a common goal.
Previous editions of the Proceedings published under the title "Economy of eastern Croatia – yesterday, today, tomorrow" and indexed in THOMSON REUTERS, Web of Science®, EBSCOhost, EconPapers.
ENG